Time-course of pain and salivary opiorphin release in response to oral capsaicin differ in burning mouth syndrome patients, temporomandibular disorders patients and control subjects - Alajbeg, Iva Z.; Vrbanovic, Ema; Alajbeg, Ivan; Orabovic, Ivan; Naka, Klara; Mrla, Antonija; Boucher, Yves (Clinical oral investigations, 2024)
Objectives Opiorphin is an analgesic peptide released by salivary glands and capsaicin an agonist of TRPV1 receptors eliciting burning sensations. The primary objective of this study was to assess opiorphin release after stimulation of the tongue by capsaicin (STC). The secondary objectives were to compare opiorphin release after STC in 3 groups of subjects [healthy (CTRL), Burning Mouth Syndrome (BMS), painful Temporomandibular disorders (TMDp)] and pain evoked by STC in these 3 groups. Materials and methods Salivary opiorphin was assessed with high-performance liquid chromatography at 3 different time points (baseline, after 5 min and 20 min of STC). Pain was self-reported on a (0–10) numeric rating scale. Results Three groups ( N = 16) of adults were recruited at the Clinical Hospital Centre and School of Dental Medicine in Zagreb. Opiorphin levels were higher (1) in TMDp compared to CTRL in 1st (2.23 ± 1.72 pg/ul vs. 0.67 ± 0.44 pg/ul, p = 0.002) and 3rd sampling (2.44 ± 2.01 pg/ul vs. 0.74 ± 0.52 pg/ul, p = 0.020) and (2) within BMS group at 3rd sampling vs. baseline ( p < 0.025). Pain scores were higher in BMS compared to TMDp ( p < 0.025) and CTRL ( p < 0.025). Conclusion This study evidenced (1) a differential basal amount of opiorphin in two pain conditions and control subjects (2) a differential kinetic of release of opiorphin after STC in CTRL, BMS and TMDp (3) a differential pain perception after STC in BMS and TMDp vs. CTRL, which can provide a readout for animal models. Clinical relevance The specific regulation of opiorphin release in patients with orofacial painful conditions provides valuable insights for clinicians and researchers in physiology and pathology and encourages further research in this area. Trial registration ClinicalTrials.gov NCT04694274. Registered on 01/05/2021.